The efficacy and safety of dachaihu decoction in the treatment of type 2 diabetes mellitus: A systematic review and meta-analysis - Zhang, Zehua; Leng, Yulin; Fu, Xiaoxu; Yang, Chan; Xie, Hongyan; Yuan, Haipo; Liang, Qingzhi; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a clinical metabolic syndrome characterized by persistent hyperglycemia. Dachaihu Decoction (DCHD) is a traditional Chinese medicine formula that has been gradually used in T2DM treatment. A comprehensive analysis on the efficacy and safety of DCHD in T2DM treatment is necessary. Objective: This meta-analysis aimed to systematically assess the clinical efficacy and safety of DCHD in the T2DM treatment and provide a reference for subsequent research and clinical practice. Methods: Both Chinese and English databases were searched from their inceptions to November 2021. All retrieved studies were screened according to inclusion and exclusion criteria and randomized controlled trials about DCHD on T2DM were enrolled. The quality of the literature was assessed using the bias risk assessment tool in the Cochrane Handbook. Review Manager 5.4 and Stata 16.0 were used for meta-analysis. Sources of heterogeneity were also explored by using meta-regression and subgroup analysis. Funnel plot and Egger's test were used to assess publication bias and the evidence quality was assessed by GRADE. Results: 17 eligible studies, involving 1525 patients, were included in this study. Compared with conventional treatment, combined treatment with DCHD was significantly better in improving HbA1c, FBG, 2hPG, TC, TG, LDL-C, HOMA-IR, HOMA-β and BMI. When DCHD used alone, it had a similar efficacy to conventional treatment in HbA1c and FBG. It can also reduce 2hPG, even if not as effective as conventional treatment. Due to the small number of included studies, it is unclear whether DCHD used alone has an improving effect on lipid metabolism, BMI, HOMA-IR and HOMA-β. Conclusions: Based on this meta-analysis, we found that the combination with DCHD in the T2DM treatment has more advantages than conventional treatment alone, which can further regulate the glucose and lipid metabolism, reduce insulin resistance, improve islet function and lower BMI. DCHD alone also plays a certain role in regulating glucose. Meanwhile, DCHD is relatively safe. However, limited by the quality and quantity of included studies, the efficacy and safety of DCHD remain uncertain. More high-quality studies are still needed to provide more reliable evidence for the clinical application of DCHD.